CAMP signalling decreases p300 protein levels by promoting its ubiquitin/proteasome dependent degradation via Epac and p38 MAPK in lung cancer cells. Issue 9 (20th March 2013) - Jeong, Min-Jae; Kim, Eui-Jun; Cho, Eun-Ah; Ye, Sang-Kyu; Kang, Gyeong Hoon; Juhnn, Yong-Sung
Abstract : The transcriptional coactivator p300 functions as a histone acetyltransferase and a scaffold for transcription factors. We investigated the effect of cAMP signalling on p300 expression. The activation of cAMP signalling by the expression of constitutively active Gαs or by treatment with isoproterenol decreased the p300 protein expression in lung cancer cells. Isoproterenol promoted the ubiquitination and subsequent proteasomal degradation of p300 in an Epac‐dependent manner. Epac promoted p300 degradation by inhibiting the activity of p38 MAPK. It is concluded that cAMP signalling decreases the level of the p300 protein by promoting its ubiquitin–proteasome dependent degradation, which is mediated by Epac and p38 MAPK, in lung cancer cells. Abstract : cAMP signalling inhibits p300 protein expression in lung cancer cells. cAMP signalling promotes the ubiquitin/proteasome‐mediated degradation of p300. cAMP signalling promotes p300 degradation via Epac and p38 MAPK.